Elaboração e aplicação de atividades investigativas na formação inicial de professores da educação básica em astronomia - Vidigal, Wesley Quintiliano (2019)
In this work we analyze the insertion of investigative activities on topics of basic Astronomy, such as the shape of the Earth, gravitational field, day and night, terrestrial orbit, seasons of the year, Solar System and sky observation, in a mini-course of initial training applied to two classes of undergraduate students in Biological Sciences of the Universidade Federal do Espírito Santo.